Step-by-step explanation
First triangle
Since it is a right triangle, we can use the trigonometric ratio cos(θ) to find the length c.
![\cos(\theta)=\frac{\text{ Adjacent side}}{\text{ Hypotenuse}}](https://img.qammunity.org/2023/formulas/mathematics/college/yzzqv1z5pan2hls7w6xmcv39pwjdcc9yoe.png)
So, we have:
![\begin{gathered} \cos(\theta)=\frac{\text{ Adjacent side}}{\text{ Hypotenuse}} \\ \cos(45°)=(c)/(7) \\ \text{ Multiply by 7 from both sides} \\ \cos(45\degree)\cdot7=(c)/(7)\cdot7 \\ 7\cos(45\degree)=c \\ (7√(2))/(2)=c \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/155p9br1aciz7ytdztb8xvzjlmbq9vwuft.png)
Second triangle
Since it is a right triangle, we can use the trigonometric ratio cos(θ) to find the length a.
So, we have:
![\begin{gathered} \cos(\theta)=\frac{\text{ Adjacent side}}{\text{ Hypotenuse}} \\ \cos(60°)=(a)/(2) \\ \text{ Multiply by 2 from both sides} \\ \cos(60°)\cdot2=(a)/(2)\cdot2 \\ 2\cos(60\degree)=a \\ 2\cdot(1)/(2)=a \\ 1=a \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m26bt0igh1ns003m26pwucxfurj3k3u7fb.png)
Answer
![\begin{gathered} c=(7√(2))/(2) \\ a=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bibogk4x29o08sdkuv1fx4dxk15payrki8.png)